PENGGUNAAN ISTILAH ASING VERSUS KEBANGGAAN PADA BAHASA NASIONAL - Haryani, Heni (JURNAL KEBANGSAAN RI, 2024)
Many foreign terms are found scattered in society where the society is still traditional. Especially the use of foreign terms taken from English which for some people are not very familiar to the public. These terms are scattered around and are used to label shops, cafes or stalls that provide local products to local consumers. It can be understood that the use of this term indicates the name of the trading activity or business activity carried out as an identity that shows the brand of the activity. This method is used as an effort to show that the stall or shop has its own class. There is pride for its users even though they actually show distrust and respect for their own language. Based on this reality, this study aims to clearly reveal the use of foreign terms used by local business people. The method used is descriptive qualitative to understand the issues that are the subject and object of the study. The results show that the use of foreign terms represents the social class of the users who come from the upper class with a fairly high economic and educational level.